NiBi sodium-ion battery negative electrode material and preparation method and application thereof

CN122930889APending Publication Date: 2026-10-16JINGGANGSHAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610971053.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-01
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]针对上述Bi基负极体积膨胀严重、反应动力学迟缓以及Bi与S/Se形成的化合物导电性差等问题,本发明提供了一种NiBi钠离子电池负极材料及其制备方法和应用

Benefits of technology

(1)本发明提供了一种NiBi钠离子电池负极材料,该材料为具有六方晶体结构(空间群P63/mmc)的NiBi金属间化合物。通过将储钠惰性的过渡金属Ni与Bi合金化,Ni作为惰性缓冲骨架有效抑制了Bi在充放电过程中的体积膨胀,同时该材料具有金属导电性和三维Na+离子扩散通道,显著提升了材料的电子导电率和反应动力学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930889A_ABST
    Figure CN122930889A_ABST
Patent Text Reader

Abstract

The application provides a NiBi sodium ion battery negative electrode material and a preparation method and application thereof. The NiBi sodium ion battery negative electrode material is a NiBi intermetallic compound with a hexagonal crystal structure, and the space group is P63 / mmc. The material presents a multi-level structure in which nanoscale primary particles (<200 nm) are agglomerated into micron-level secondary particles (0.5-10 µm). The application further discloses a preparation method of the material. The method is a batch high-energy ball milling method, and uses Ni and Bi elemental powder as raw materials to obtain the target product under inert gas protection. The method is simple in process and suitable for large-scale production. When the negative electrode material is used as a sodium ion battery negative electrode active material, it exhibits high initial coulombic efficiency, excellent rate performance and super-long cycle stability, and has a capacity retention rate of 95.3% after 10000 cycles at 0.5 A g ‑ ¹, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sodium-ion battery technology, and in particular to a NiBi sodium-ion battery anode material, its preparation method, and its application. Background Technology

[0002] With the rapid development of the global new energy industry, the problems of tight lithium resource supply and uneven distribution have become increasingly prominent, leading to a continuous rise in lithium salt prices, which to some extent restricts the promotion and application of lithium-ion batteries in large-scale energy storage and other fields. Sodium and lithium belong to the same main group, have similar physicochemical properties, and similar electrode potentials. Moreover, sodium resources are abundant in the earth's crust, widely distributed, and inexpensive, making sodium-ion batteries show broad application prospects in large-scale energy storage and low-speed electric vehicles.

[0003] However, the ionic radius of sodium ions is significantly larger than that of lithium ions, a fundamental difference that poses a serious challenge to the design of electrode materials. The larger ionic radius not only leads to sluggish solid-state diffusion kinetics but also easily induces severe lattice strain and volume changes during sodium insertion / extraction, thereby affecting the structural stability and cycle life of the electrode. Bismuth (Bi) metal, due to its high theoretical specific capacity (based on the Na3Bi phase, a mass specific capacity of 385 mAh g⁻¹), is a suitable candidate for electrode material design. - ¹, with a volumetric capacity of up to 1089 mAh / cm³ - Bi anodes have attracted much attention due to their volume expansion during charging and discharging. However, the volume expansion effect of Bi during charging and discharging can cause the active material to detach from the current collector, become pulverized, and continuously expose fresh surfaces, exacerbating side reactions with the electrolyte and ultimately leading to deactivation of the active material and rapid capacity decay. Therefore, effectively buffering the volume expansion of Bi-based anodes and accelerating their reaction kinetics is key to developing high-performance Bi anodes.

[0004] To address the aforementioned issues, related research has attempted to alloy Bi with elements such as sulfur (S) and selenium (Se) to construct compounds with layered structures (e.g., Bi₂S₃). Theoretically, these layered structures can provide wider diffusion channels for sodium ions, which is beneficial for improving rate performance, and some compounds even show a higher theoretical specific capacity compared to pure Bi. However, since elements such as S and Se have much higher electronegativity than Bi, the resulting compounds are mostly semiconductors, resulting in a significant reduction in intrinsic electronic conductivity. This leads to increased electrode polarization, ultimately weakening the energy density output of the entire battery. Therefore, developing a novel Bi-based anode material that combines high specific capacity, excellent rate performance, and long cycle stability is of great significance for promoting the development of sodium-ion batteries. Summary of the Invention

[0005] To address the problems of severe volume expansion, sluggish reaction kinetics, and poor conductivity of the Bi-S / Se compound in Bi-based anodes, this invention provides a NiBi anode material for sodium-ion batteries, its preparation method, and its applications. This invention employs an intermittent high-energy ball milling method to alloy metallic Bi with the sodium-inert transition metal Ni, synthesizing a NiBi intermetallic compound with a hexagonal crystal structure (space group P63 / mmc). When used as the active material for sodium-ion batteries, the introduction of Ni not only effectively buffers the volume expansion of Bi during charge and discharge but also significantly improves the electronic conductivity and structural stability of the material. Sodium-ion batteries prepared from this anode material exhibit high initial coulombic efficiency, excellent rate performance, and ultra-long cycle stability (at 0.5 A g). - ¹After 100 cycles at current density, the capacity retention rate is as high as 95.6%, which can fully meet the application requirements of high-performance energy storage equipment.

[0006] The first aspect of the present invention provides a NiBi sodium-ion battery anode material, wherein the NiBi sodium-ion battery anode material is an intermetallic compound with a hexagonal crystal structure and a space group of P63 / mmc.

[0007] Furthermore, the material is a micron-sized secondary particle, which is formed by the aggregation of primary nanoparticles with a particle size of less than 200 nm, and the particle size of the secondary particle is 0.5~10 µm.

[0008] The second aspect of this invention provides a method for preparing a NiBi sodium-ion battery anode material, the specific steps of which include: S1: Place the elemental powders of Ni and Bi in a ball mill jar and perform high-energy ball milling at a speed of 400~1000 rpm under inert gas protection. S2: After ball milling, the sample is cooled to room temperature and taken out in an inert gas atmosphere to obtain the NiBi sodium ion battery anode material.

[0009] Furthermore, in step S1, the molar ratio of Ni elemental powder to Bi elemental powder is 1:1.

[0010] Furthermore, the inert gas mentioned in step S1 includes argon and nitrogen.

[0011] Furthermore, the inert gas mentioned in step S1 is argon.

[0012] Furthermore, the high-energy ball milling speed in step S1 is 600~700 rpm, the high-energy ball milling is carried out intermittently, the ball milling balls are stainless steel balls, and after each ball milling for 25 min~35 min, it stops for 20 min~30 min, and the total effective ball milling time is 10 h~20 h.

[0013] Furthermore, the high-energy ball milling speed in step S1 is 650 rpm, the high-energy ball milling is carried out intermittently, the ball milling balls are stainless steel balls, and the milling is stopped for 25 minutes after each 30-minute milling session, with a total effective milling time of 15 hours.

[0014] The third aspect of this invention provides an application of the NiBi sodium-ion battery anode material described in the first aspect in sodium-ion batteries.

[0015] A fourth aspect of the present invention provides a NiBi sodium-ion battery anode, the anode comprising a current collector and an active material layer coated on at least one surface of the current collector; wherein the active material layer comprises a NiBi sodium-ion battery anode material, a conductive agent, and a binder, and the mass ratio of the NiBi sodium-ion battery anode material, the conductive agent, and the binder is 6.5-9.5:0.5-2.0:0.5-2.0; the loading amount of the NiBi sodium-ion battery anode material on the current collector is 1-10 mg cm⁻¹. - ².

[0016] The fifth aspect of the present invention provides a NiBi sodium-ion battery, the NiBi sodium-ion battery comprising a positive electrode, a negative electrode, an electrolyte, and a separator; wherein the negative electrode is the negative electrode of the NiBi sodium-ion battery.

[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention provides a NiBi sodium-ion battery anode material, which is a NiBi intermetallic compound with a hexagonal crystal structure (space group P63 / mmc). By alloying the sodium-storing inert transition metal Ni with Bi, Ni acts as an inert buffer framework to effectively suppress the volume expansion of Bi during charging and discharging. At the same time, this material has metallic conductivity and three-dimensional Na+. + Ion diffusion channels significantly improve the electronic conductivity and reaction kinetics of the material.

[0018] (2) The material of the present invention presents a multi-level structure from "nanoscale primary particles (<200 nm) to micron-scale secondary particles (0.5-10 µm)," which not only shortens the solid-state diffusion path of sodium ions and is beneficial to fast charging performance, but also facilitates electrode coating and processing and realizes high-activity material loading.

[0019] (3) The present invention employs an intermittent high-energy ball milling method, using elemental Ni and Bi powders as raw materials, and synthesizes the target product in a step under inert gas protection. This method is simple, does not require high-temperature sintering, has low energy consumption, is suitable for large-scale production, and produces products with high phase purity and controllable crystal structure.

[0020] (4) When the material of the present invention is used as the negative electrode active material of sodium-ion battery, it exhibits high initial coulombic efficiency, excellent rate performance and ultra-long cycle stability, and has excellent interfacial compatibility with Diglyme-based ether electrolytes.

[0021] (5) A full cell assembled using the NiBi material of the present invention as the negative electrode, at 0.5 A g - ¹The initial discharge specific capacity at current density reaches 102.7 mAh g⁻¹ - ¹ With an average operating voltage of approximately 2.86 V, the capacity retention rate reaches 95.6% after 100 cycles, demonstrating promising prospects for practical applications. Attached Figure Description

[0022] Figure 1 The image shows the X-ray diffraction pattern of the NiBi intermetallic compound prepared in Example 1.

[0023] Figure 2 This is a scanning electron microscope image of the NiBi intermetallic compound prepared in Example 1.

[0024] Figure 3 This is a transmission electron microscope (TEM) image of the NiBi intermetallic compound prepared in Example 1.

[0025] Figure 4 The graph shows the sodium storage charge-discharge curves of the NiBi sodium-ion battery negative electrode in Example 2.

[0026] Figure 5 The graph shows the sodium storage cycle performance of the NiBi sodium-ion battery negative electrode in Example 2.

[0027] Figure 6 This is a charge-discharge curve of a NiBi sodium-ion full cell.

[0028] Figure 7 The graph shows the cycle performance of a NiBi sodium-ion full cell. Detailed Implementation

[0029] To enable those skilled in the art to better understand the technical solutions in this specification, the technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this specification, and not all embodiments. The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be considered as specifically disclosed herein.

[0030] The first aspect of the present invention provides a NiBi sodium-ion battery anode material, wherein the NiBi sodium-ion battery anode material is an intermetallic compound with a hexagonal crystal structure and a space group of P63 / mmc.

[0031] In one specific embodiment of the present invention, the NiBi sodium-ion battery anode material is a micron-sized secondary particle, which is formed by the aggregation of primary nanoparticles with a particle size of less than 200 nm, and the particle size of the secondary particle is 0.5~10 µm.

[0032] The second aspect of this invention provides a method for preparing a NiBi sodium-ion battery anode material, the specific steps of which include: S1: Place the elemental powders of Ni and Bi in a ball mill jar and perform high-energy ball milling at a speed of 400~1000 rpm under inert gas protection. S2: After ball milling, the sample is cooled to room temperature and taken out in an inert gas atmosphere to obtain the NiBi sodium ion battery anode material.

[0033] In a specific embodiment of the present invention, the molar ratio of Ni elemental powder to Bi elemental powder in step S1 is 1:1.

[0034] In one specific embodiment of the present invention, in order to protect the target product and improve the purity of the target product, the inert gas in step S1 includes argon and nitrogen; preferably, the inert gas in step S1 is argon.

[0035] In a specific embodiment of the present invention, the high-energy ball milling speed in step S1 is 600~700 rpm, the high-energy ball milling is carried out intermittently, the ball milling balls are stainless steel balls, and after each ball milling for 25 min~35 min, it stops for 20 min~30 min, and the total effective ball milling time is 10 h~20 h.

[0036] In a preferred embodiment of the present invention, the high-energy ball milling speed in step S1 is 650 rpm, the high-energy ball milling is carried out intermittently, the ball milling balls are stainless steel balls, and after each 30 min of ball milling, it is stopped for 25 min for heat dissipation, and the total effective ball milling time is 15 h.

[0037] The third aspect of this invention provides an application of NiBi sodium-ion battery anode material in sodium-ion batteries.

[0038] A fourth aspect of the present invention provides a NiBi sodium-ion battery anode, the sodium-ion battery anode comprising a current collector and an active material layer coated on at least one surface of the current collector; wherein the current collector comprises copper foil or aluminum foil; the active material layer comprises NiBi sodium-ion battery anode material, a conductive agent, and a binder, and the mass ratio of the NiBi sodium-ion battery anode material, the conductive agent, and the binder is 6.5-9.5:0.5-2.0:0.5-2.0; the loading amount of the NiBi sodium-ion battery anode material on the current collector is 1-10 mg cm⁻¹. - ².

[0039] In a preferred embodiment of the present invention, the mass ratio of the NiBi sodium-ion battery anode material, the conductive agent, and the binder is 7:2:1, and the loading of the NiBi sodium-ion battery anode material on the current collector is 1.5 mg / cm³. - ².

[0040] The fifth aspect of the present invention provides a NiBi sodium-ion battery, the NiBi sodium-ion battery comprising a positive electrode, a negative electrode, an electrolyte, and a separator; wherein the negative electrode is the negative electrode of the NiBi sodium-ion battery.

[0041] The present invention will be described in detail below through examples, but the scope of protection of the present invention is not limited thereto. In the following examples, the pharmaceuticals and agents are all conventional commercially available products.

[0042] Example 1 Preparation of NiBi intermetallic compound anode materials This invention employs an intermittent high-energy ball milling method to prepare NiBi intermetallic compound anode materials. The specific steps are as follows: Step 1: Weighing and premixing raw materials The raw materials were accurately weighed according to the atomic ratio of Ni to Bi of 1:1. Specifically, 0.658 g of nickel powder (Ni, purity ≥99.9%, particle size ≤200 nm) and 2.342 g of bismuth powder (Bi, purity ≥99.9%, particle size ≤200 nm) were weighed using an electronic analytical balance with a total mass of 3.000 g.

[0043] Step 2, Filling and Atmosphere Protection The mixed powder obtained in step 1 is loaded into a stainless steel ball mill jar along with 30 stainless steel grinding balls with a diameter of 10 mm. The ball mill jar is then transferred to a glove box filled with high-purity argon gas (purity ≥99.999%). The jar lid is sealed under argon protection to ensure that the entire ball milling process is conducted in an inert atmosphere to prevent oxidation of the raw materials.

[0044] Step 3: Intermittent high-energy ball milling The sealed grinding jar is installed on a planetary high-energy ball mill, and high-energy ball milling is performed at a speed of 650 rpm. The ball milling process adopts an intermittent operation mode: after 30 minutes of continuous ball milling, it is stopped for 25 minutes for heat dissipation, and the total effective ball milling time is 5-15 hours.

[0045] Step 4: Product Collection After ball milling, allow the milling jar to cool naturally to room temperature (approximately 1-2 hours). Open the milling jar in an argon-filled glove box and scrape off the powder product from the jar walls and bottom to obtain a black powdery NiBi intermetallic compound anode material.

[0046] Example 2 Preparation of NiBi sodium-ion battery anode sheet In this embodiment of the invention, the powdered NiBi intermetallic compound prepared in Example 1 is used as the active material to prepare a NiBi sodium-ion battery negative electrode sheet. The negative electrode sheet includes a current collector and an active material layer coated on the surface of the current collector. The active material layer includes a negative electrode material, a conductive agent, and a binder, as detailed below: In this embodiment, copper foil is used as the current collector, the NiBi sodium-ion battery anode material prepared in Example 1 is used as the active material, conductive carbon black (Super P) is used as the conductive agent, and sodium carboxymethyl cellulose (Na-CMC) is used as the binder. 140 mg of NiBi anode material, 40 mg of Super P, and 20 mg of Na-CMC are weighed out at a mass ratio of 7:2:1, and an appropriate amount of deionized water is added. The mixture is then thoroughly ground in an agate mortar until a uniform slurry with suitable flowability and viscosity is formed.

[0047] The above slurry was uniformly coated onto the surface of the copper foil current collector using a doctor blade coating method, controlling the coating thickness to ensure that the surface loading of the active material after drying was 1.5 mg / cm². - ². The coated electrode sheets are transferred to a vacuum drying oven and dried under vacuum at 60°C for 10 hours. After drying, the electrode sheets are removed, rolled flat by a roller press, and then cut into circular electrode sheets with a diameter of 10 mm, thus obtaining the NiBi sodium-ion battery negative electrode sheet.

[0048] Analysis example 1 X-ray diffraction (XRD) pattern analysis To determine the crystal structure of the NiBi intermetallic compound anode material prepared in Example 1 and to illustrate the effect of ball milling time on crystal formation, this analysis example uses powder X-ray diffraction (XRD, Cu Kα radiation, λ=1.5406 Å) to perform phase analysis on the black powdered NiBi intermetallic compound obtained in Example 1 at different ball milling times (0h, 5h, 10h, 15h). The results are as follows: Figure 1 As shown.

[0049] Figure 1 The images show the X-ray diffraction (XRD) patterns of the products obtained from different ball milling times (0 h, 5 h, 10 h, 15 h) in Example 1. Figure 1 As can be seen from the data, different products obtained from ball milling for different durations in Example 1 exhibit different diffraction peaks. Before ball milling, the characteristic diffraction peaks of the raw materials Ni and Bi are sharp and clear, indicating that the raw materials have good crystallinity. After ball milling for 5 hours, diffraction peaks of NiBi3 and NiBi can be detected, indicating that Ni and Bi have undergone alloying reaction within the 5-hour ball milling time, but the reaction is not yet complete, and the product is a mixture of NiBi3 and NiBi, with a small amount of unreacted Ni and Bi residue. After ball milling for 10 hours, the diffraction peaks of Ni and Bi completely disappear, and only the diffraction peak of NiBi is detected, indicating that Ni and Bi have been basically completely converted into NiBi intermetallic compounds. Continuing to extend the ball milling time to 15 hours, the XRD pattern of the product shows no significant change compared to 10 hours, and the position and relative intensity of the diffraction peaks are basically the same, indicating that the product phase has become stable, and further extending the ball milling time will not cause phase transformation or the formation of impurity phases. In summary, the material prepared in Example 1 is a hexagonal (space group: P63 / mmc) NiBi intermetallic compound.

[0050] Analysis example 2 Field emission scanning electron microscopy (SEM) image analysis The microstructure of the black powdery NiBi intermetallic compound obtained by ball milling for 15 h in Example 1 was observed using field emission scanning electron microscopy (SEM). The results are as follows: Figure 2As shown in the image, the black powdery NiBi intermetallic compound obtained in Example 1 exhibits a micron-sized secondary particle morphology with a particle size distribution ranging from 0.5 µm to 10 µm. These micron-sized secondary particles are actually formed by the tight aggregation of even smaller nano-sized primary particles (particle size less than 200 nm). This result indicates that under the intense mechanical impact of high-energy ball milling, the original Ni and Bi elemental powders are first refined to the nanoscale. Subsequently, during repeated cold welding and fracture processes, the nano-sized primary particles further aggregate and assemble into micron-sized secondary particles, forming a unique "nano-micro" multi-level structure. This multi-level structure offers the following advantages: ① Nanoscale primary particles (<200 nm) significantly shorten the solid-state diffusion path of sodium ions, which helps reduce electrode polarization and improve the rate performance of the battery; ② Micrometer-scale secondary particles (0.5 µm ~ 10 µm) facilitate the coating and compaction of electrode slurry, enabling higher surface loading of active material; ③ The dense packing structure inside the secondary particles facilitates electrical contact between particles, effectively reducing electrode internal resistance and improving cycle stability. This structural design provides an important microstructural basis for the subsequent excellent sodium storage performance.

[0051] Analysis example 3 Transmission electron microscopy (TEM) image analysis To further elucidate the microstructure and crystal structure of the prepared NiBi product, transmission electron microscopy (TEM) was used to further characterize the morphology and crystal structure of the black powdery NiBi intermetallic compound obtained by ball milling for 15 h in Example 1. The results are as follows: Figure 3 As shown in the figure, the NiBi product exhibits an irregular granular morphology with distinct particle edges, consistent with SEM observations, further confirming that the black powdery NiBi intermetallic compound is polycrystalline.

[0052] Application Example 1 Testing of Sodium Storage Performance and Electrochemical Performance of NiBi Anode Material CR2032 coin cell half-cells were assembled in a glove box filled with high-purity argon. The NiBi anode prepared in Example 2 was used as the working electrode, with a sodium metal sheet as the counter and reference electrode. A glass fiber and PP membrane were laminated as the separator, and 1 mol / L NaPF6 dissolved in diethylene glycol dimethyl ether was used as the electrolyte. The charge / discharge voltage window was 0.01 V to 1.8 V (vs. Na). + / Na), the test temperature was 25±2 °C.

[0053] The electrochemical test results are as follows: Figure 4 It can be seen that at 0.5 Ag -¹At the given current density, the battery's first-cycle discharge specific capacity is 347.8 mAh g. - ¹, The charging specific capacity is 316.8 mAh g - ¹, the initial Coulomb efficiency is 91.09%. (From...) Figure 5 It can be seen that at 0.5 Ag - The long-term cycling stability of NiBi was evaluated at a current density of ¹. After stabilization in the second cycle, the charge specific capacity was 304.2 mAh g⁻¹. - ¹. After 10,000 cycles, the charging capacity remains at 290.0 mAh g. - ¹, with a capacity retention of 95.3%. This excellent cycling stability demonstrates that the NiBi electrode possesses good structural integrity and high reversibility.

[0054] Application Example 2 Assembly and electrochemical performance testing of sodium-ion full cells (1) Na3V2(PO4)3 positive electrode plate The positive electrode material Na3V2(PO4)3 used in this embodiment is a commercially available sodium vanadium phosphate positive electrode sheet.

[0055] (2) Pre-sodium treatment of NiBi anode To compensate for the irreversible sodium loss during the first cycle, the NiBi anode sheet prepared in Example 2 was pre-sodiumized. Pre-sodiumization was achieved by short-circuiting the NiBi electrode with a sodium metal sheet in a 1 M NaPF6 in diglyme electrolyte for a certain period of time.

[0056] (3) Full battery assembly and testing Using pre-sodium-treated NiBi as the negative electrode and the aforementioned Na3V2(PO4)3 as the positive electrode, a CR2032 type full cell was assembled with a negative electrode to positive electrode mass ratio of 1:2. The electrolyte and separator were the same as in Application Example 1.

[0057] The electrochemical test results are as follows: at 0.5 A g - At a current density of ¹, the initial discharge specific capacity is 102.7 mAhg. - ¹(based on the mass of the positive electrode active material), the initial coulombic efficiency is as high as 95.6%, and the average operating voltage is approximately 2.86 V (e.g., Figure 6 As shown). Figure 7 As shown, at 0.5 A g - ¹After 100 cycles, the capacity retention rate reached 95.6%, demonstrating excellent cycling stability.

[0058] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any changes or substitutions conceived without inventive effort should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope defined in the claims.

[0059] The above-described embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application.

Claims

1. A NiBi sodium-ion battery anode material, characterized in that, The NiBi sodium-ion battery anode material is an intermetallic compound with a hexagonal crystal structure and a space group of P63 / mmc.

2. The NiBi sodium-ion battery anode material according to claim 1, characterized in that, The material is micron-sized secondary particles, which are formed by the aggregation of primary nanoparticles with a particle size of less than 200 nm, and the particle size of the secondary particles is 0.5~10 µm.

3. A method for preparing a NiBi sodium-ion battery anode material, characterized in that, The specific steps include: S1: Place the elemental powders of Ni and Bi in a ball mill jar and perform high-energy ball milling at a speed of 400~1000 rpm under inert gas protection; S2: After ball milling, the sample is cooled to room temperature and taken out in an inert gas atmosphere to obtain the NiBi sodium ion battery anode material.

4. The method according to claim 3, characterized in that, In step S1, the molar ratio of Ni elemental powder to Bi elemental powder is 1:

1.

5. The method according to claim 3, characterized in that, The inert gas mentioned in step S1 includes argon and nitrogen.

6. The method according to claim 3, characterized in that, The high-energy ball milling speed in step S1 is 600~700 rpm. The high-energy ball milling is carried out intermittently. The ball milling balls are stainless steel balls. After each ball milling session of 25 min~35 min, the milling is stopped for 20 min~30 min. The total effective ball milling time is 10 h~20 h.

7. The method according to claim 6, characterized in that, The high-energy ball milling speed in step S1 is 650 rpm. The high-energy ball milling is carried out intermittently, and the milling balls are stainless steel balls. After each 30-minute milling session, the milling is stopped for 25 minutes, and the total effective milling time is 15 hours.

8. The application of the NiBi sodium-ion battery anode material according to claim 1 or 2 in sodium-ion batteries.

9. A NiBi sodium-ion battery negative electrode, characterized in that, The negative electrode includes a current collector and an active material layer coated on at least one surface of the current collector; wherein the active material layer comprises NiBi sodium-ion battery negative electrode material, a conductive agent, and a binder, and the mass ratio of the NiBi sodium-ion battery negative electrode material, the conductive agent, and the binder is 6.5-9.5:0.5-2.0:0.5-2.0; the loading amount of the NiBi sodium-ion battery negative electrode material on the current collector is 1-10 mg / cm³. - ².

10. A NiBi sodium-ion battery, characterized in that, The NiBi sodium-ion battery includes a positive electrode, a negative electrode, an electrolyte, and a separator; wherein the negative electrode is the negative electrode of the NiBi sodium-ion battery.